Methodology for technological selection in building production using the life-cycle cost concept - Silva, Maria Angélica Covelo (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The selection of technological alternatives for the conception and development of building projects has become an increasingly complex decision for promoters, designers and building contractors. The variables of the decision making process were identified in this paper by focusing techonology in a competitive logic, and by qualifuing the technology selection process as a quality management element in the developing phase of building. The main goal was to develop a model to aid decision-makers with approaches that, untilnow, hadn’t been incorporated to the production of buildings, although desirable in face of the needs of the all agents in the procuction process. The needs of users production agents were identified by characterization methods of compretitive strategies, market segments and the performance expectancy of the products during their life-cycle, focusing housing construction. The methodology establishes a model of an information system shared among the agents which develop instruments to define performance criteria of the building products during their life-cycle. This includes the economical performance, in other words, theirs performance refering to the costs of operation and maintenance activities.